Penerapan Media Penjepit Jemuran untuk Menanamkan Sifat Kejujuran Anak Usia Dini - Veryawan veryawan (Kiddo: Jurnal Pendidikan Islam Anak Usia Dini, 2021)
This study aims to review the moral development of children. In moral attitudes and behavior, it is implied that the values ​​adhered to are related to the value of something that is said to be good and bad, right and wrong, appropriate, and should happen. This research was conducted at RA Al Ikhlas Konggo Deli Serdang. The subjects of this study were students of RA Al Ikhlas Konggo in group B III totaling 15 people consisting of 6 women and 9 men with a recreational theme. The research used is classroom action research. In interpreting the results of the analysis carried out during the process of clamping clotheslines, researchers used percentage analysis to obtain results about increasing the honesty nature of early childhood through the application of clothesline clamp media and analysis tests using the average child and the criteria for mastery learning children. In the study, it is considered successful if the results achieved by the child have reached 80% in the application of clothesline clamp media to instill honesty in early childhood.